ON THE ISSUE OF THE SYSTEM OF CIVIL-LEGAL MEANS OF INFLUENCE ON INVESTMENT ACTIVITY - N. A. Aizetullova (Russian Journal of Economics and Law)
The article views the legal tools expressed in civil-law means, which exercise the investment regulation. For the first time in juridical practice the notion of civil-law levers for investment activity are presented. The systemic character of these legal levers is grounded. The author expresses opinion of the inter-sector interaction between the civil-law levers for investment activity and the legal means of other areas of law.